Assessment of the Usability of Devices with BLE Interface In Automatic Access Control Systems - Artur ARCIUCH (Communications of International Proceedings, 2022)
Access control systems are widely used in organizations. Specialized cards and readers are used to control access. The use of cards and readers equipped with a BLE interface in such systems eliminates the need to bring the card closer to the reader in order to access the organization's resource. The article evaluates the usability of devices with the BLE interface in automatic access control systems, based on the accuracy and repeatability of the RSSI parameter measurement.
Keywords: BLE; RSSI; distance measurement